ANALYSIS OF COST CALCULATION IN THE CONSTRUCTION PROJECT OF KAPAS – GLENDENG 8 BRIDGE IN BOJONEGORO DISTRICT DUE TO TIME ACCELERATION USING THE CRASHING METHOD WITH ALTERNATIVE ADDITION OF WORKING HOURS - Ariyanto, Subkhan; Tjendani, Hanie Teki; Witjaksana, Budi (Transpublika Publisher, 2024)
Infrastructure development plays a very important role as capital in efforts to stimulate increased economic productivity, both at the national and regional levels, as well as reducing unemployment, alleviating people from poverty and of course improving the standard of living of the community at large. Delays in completing a project are a problem that often arises and can have an impact on the entire work, especially with time delays resulting in increased costs which can be detrimental to many parties. This delay also occurred in the Kapas-Glendeng 8 bridge construction project, Bojonegoro Regency. In anticipation of these delays, it is necessary to accelerate time and costs. In this research the author uses the crashing method with the alternative of increasing working hours. The crashing method is a way of estimating cost variables to determine the maximum and most economical reduction in the duration of an activity that is still possible to reduce. The research results showed that the total time and cost of the project required after crashing was 174 calendar days with a cost under accelerated conditions of Rp. 2,555,189,555.98 with a difference of 6 calendar days from the normal duration of 180 calendar days and a fee under normal conditions of Rp. 2,548,581,990.63.